Free fatty acids and their metabolism affect function and survival of podocytes - Sieber, Jonas; Jehle, Andreas W. (Frontiers in Endocrinology, 2014)
Podocyte injury and loss critically contribute to the pathogenesis of proteinuric kidney diseases including diabetic nephropathy. Deregulated lipid metabolism with disturbed free fatty acid (FFA) metabolism is a characteristic of metabolically unhealthy obesity and type 2 diabetes and likely contributes to end-stage kidney disease irrespective of the underlying kidney disease. In the current review we summarize recent findings related to FFAs and altered renal FFA metabolism with a special focus on podocytes. We will outline the opposing effects of saturated and monounsaturated FFAs and a particular emphasis will be given to the underlying molecular mechanisms involving insulin resistance and endoplasmic reticulum homeostasis. Finally, recent data suggesting a critical role of renal FFA metabolism to adapt to an altered lipid environment will be discussed.